Currency devaluation and trade balance: Evidence from the US services trade - Cheng, Ka Ming (369 EGFR SIGNALING IMPAIRS THE ANTIVIRAL ACTIVITY OF INTERFERON-ALPHA, 2020)
This study aims to revisit the effectiveness of using currency devaluation as a policy tool to improve trade balance by estimating the exchange rate elasticities of services trade between the US and rest of the world with quarterly disaggregated services trade data from 1999 to 2015. Empirical results reveal that the impacts of currency devaluation on individual services trade are mixed and largely depend on the nature of services. Using currency devaluation to raise export services trade and reduce import services trade seems to be more effective in the long-run but not in the short-run. It is interesting to note that some individual services trades are insensitive to exchange rate changes. The estimates also reveal that most categories of services trade are income elastic and economic growth plays a key role in determining the imports and exports of services trade.